Políticas eduacacionais e a garantia do direito à educação dos adolescentes internos de João Pessoa - Oliveira, Ramon Olímpio de (2023)
The present text analyzes the role of the State in guaranteeing the right to education of inmates at the Centro Socio-Educativo Educacional Edson Mota/CSE, João Pessoa - PB. Its object of study is the investigation into the conditions of provision of education for inmate adolescents in the aforementioned socio-educational unit. Its general objective is to analyze how FUNDAC- PB implements education for adolescents based on the educational public policies contained in the Child and Adolescent Rights Guarantee System, the National Socio-Educational Assistance System, the State Socio-Educational Assistance Plan of Paraíba and in the Operational Guidelines of State Schools for adolescents. The thesis presented is that the units for the execution of socio-educational measures in Paraíba do not have a program for the execution of public educational policies related to inmate adolescents or do not guarantee the proper execution of these policies. The question that guided the research was the following: to what extent does the State guarantee the right to education of adolescents in the context of socio- educational measures through an emancipatory education that constitutes a means for the acquisition of other rights? In order to respond to the formulated problem, the thesis was structured in four chapters, in addition to the introduction and conclusion. In the first chapter, we present the methodological course of the research, explaining the method and the set of instruments, procedures and techniques for data collection and analysis. In the second chapter, we carry out a theoretical and conceptual survey about the definition of children and adolescents as different stages of life in Brazil and a brief study about the social history of children and adolescents until they are recognized as subjects of rights. In the third chapter, we discuss a little about how the construction of rights for children and adolescents in Brazil took place, studying the national and international legislation regarding the matter. In the fourth and last chapter we present the data related to the empirical research. To this end, we carried out a survey of the documents that guide the education of adolescents who are in the context of compliance with socio-educational measures, as well as a discussion about the Escola da Escolha model, which was selected as the basis for the implementation of ECIS in Paraiba. Having carried out this survey, we set out to discuss the Socio-Educational Center Edson Mota and the Escola Cidadã Integral Socio-educativa Almirante Saldanha (EAS) through an analysis of their basic documents, namely the Internal Regulations and the respective Pedagogical Political Projects. Finally, we carried out a field survey throughout the year 2022 with visits to the EAS in order to observe how education is offered to adolescents who are interns at the CSE. As a main result, we find that the Escola Cidadã Integral Socioeducativa Almirante Saldanha provides an adequate teaching model, based on an emancipatory education, but that the purpose of this education does not reach all adolescents due, mainly, but not exclusively, to the constant changes that occur throughout the school year and day to day at the unit. Some challenges arose throughout the work undertaken, among which we can highlight the logistics of transferring teenagers from their rooms to the classrooms, the search for guaranteed class time following the entry and exit times and the fight for the creation of a teaching routine even in the face of the constant changes that are present in the daily life of the CSE with the changes in class schedules and the constant arrival and departure of adolescents. We intend to continue investigating the guarantee of the right to education for these adolescents.